The Role of Job Satisfaction In Moderating The Influence of Transformational Leadership and Affective Commitment On Employee Performance - Slamet Jarwanto; Indarto Indarto; Albert Albert (Publikasi Indonesia, 2024)
The purpose of the research to identify the role of job satisfaction in moderating the influence of transformational leadership and affective commitment on employee performance. This research is a quantitative research with explanatory research type using survey method. This type of explanatory research explains the relationship between variables that have been built based on theory using hypotheses. The research steps begin based on the limitations of the problem, followed by forming a framework of thinking so that it can be used to answer the problems that are the background of this research. The temporary answer to this research error is called a hypothesis, which will be proven true by the results of analysis of the data obtained. A Sample of 76 respondents was surveyed using a census method. The data processing is done using Smart PLS 3.0. Based on the results of the analysis of research data that has been carried out, the following conclusions can be drawn: Transfomastional leadership and affective commitment significantly and positively influence employee performance. However, job satisfaction did not moderate the relationship between transformational leadership and employee performance, nor did it moderate the relationship between affective commitment and employee performance. Nonetheless, job satisfaction was found to have a significant positive impact to employee performance.